Chlorophyll fluorescence emission can screen cold tolerance of cold acclimated Arabidopsis thaliana accessions - Mishra, Anamika (Plant Methods, 2014)
BACKGROUND: An easy and non-invasive method for measuring plant cold tolerance is highly valuable to instigate research targeting breeding of cold tolerant crops. Traditional methods are labor intensive, time-consuming and thereby of limited value for large scale screening. Here, we have tested the capacity of chlorophyll a fluorescence (ChlF) imaging based methods for the first time on intact whole plants and employed advanced statistical classifiers and feature selection rules for finding combinations of images able to discriminate cold tolerant and cold sensitive plants. RESULTS: ChlF emission from intact whole plant rosettes of nine Arabidopsis thaliana accessions was measured for (1) non-acclimated (NAC, six week old plants grown at room temperature), (2) cold acclimated (AC, NAC plants acclimated at 4°C for two weeks), and (3) sub-zero temperature (ST) treated (STT, AC plants treated at -4°C for 8 h in dark) states. Cold acclimation broadened the slow phase of ChlF transients in cold sensitive (Co, C24, Can and Cvi) A. thaliana accessions. Similar broadening in the slow phase of ChlF transients was observed in cold tolerant (Col, Rsch, and Te) plants following ST treatments. ChlF parameters: maximum quantum yield of PSII photochemistry (F(V)/F(M)) and fluorescence decrease ratio (R(FD)) well categorized the cold sensitive and tolerant plants when measured in STT state. We trained a range of statistical classifiers with the sequence of captured ChlF images and selected a high performing quadratic discriminant classifier (QDC) in combination with sequential forward floating selection (SFFS) feature selection methods and found that linear combination of three images showed a reasonable contrast between cold sensitive and tolerant A. thaliana accessions for AC as well as for STT states. CONCLUSIONS: ChlF transients measured for an intact whole plant is important for understanding the impact of cold acclimation on photosynthetic processes. Combinatorial imaging combined with statistical classifiers and feature selection methods worked well for the screening of cold tolerance without exposing plants to sub-zero temperatures. This opens up new possibilities for high-throughput monitoring of whole plants cold tolerance via easy and fully non-invasive means.